IMPLEMENTASI PENUNTUTAN TERHADAP PENGEDAR SEDIAAN FARMASI ILEGAL BERDASARKAN UNDANG-UNDANG KESEHATAN DI KEJAKSAAN NEGERI TUBAN - Narita Tarasari; Maria Novita Apriyani (Universitas Labuhanbatu, 2026)
The increasing circulation of illegal pharmaceutical products, particularly Double L pills, reflects weak compliance with health regulations and poses a significant challenge to criminal law enforcement in Indonesia. This issue highlights the need for an effective prosecution mechanism as an integral part of the criminal justice system to ensure legal certainty and protect public health. This study aims to analyze the implementation of prosecution against distributors of illegal pharmaceutical products under Law Number 17 of 2023 concerning Health at the Tuban District Prosecutor’s Office, as well as to identify the obstacles encountered and the measures undertaken to address them. This research employs a normative-empirical legal research (socio-legal) method using statutory, conceptual, and empirical approaches. Data were collected through library research, field observations, and interviews with public prosecutors and other relevant officials at the Tuban District Prosecutor’s Office, and were analyzed using a qualitative descriptive approach. The findings indicate that the prosecution process has generally been conducted in accordance with the applicable legal framework through the application of the dominus litis principle. However, its effectiveness remains constrained by delays in case completion due to the repeated return of case files (P-19), differences in legal interpretation between investigators and public prosecutors, and the absence of explicit legal provisions governing the time limit for returning case files during the pre-prosecution stage. These findings underscore the need to strengthen institutional coordination among law enforcement agencies and to establish clearer legal regulations governing pre-prosecution procedures in order to enhance the effectiveness of criminal law enforcement against the illegal distribution of pharmaceutical products.Keywords: prosecution; illegal pharmaceutical products; health law; Tuban District Prosecutor’s Office; dominus litis.